The third industrial revolution in global business - Dosi, Giovanni, 1953-; Galambos, Louis (Cambridge : Cambridge University Press, 2013)
The essays in this volume probe the impact the digital revolution has had, or sometimes failed to have, on global business. Has digital technology, the authors ask, led to structural changes and greater efficiency and innovation? While most of the essays support the idea that the information age has increased productivity in global business, the evidence of a 'revolution' in the ways industries are organized is somewhat more blurred, with both significant discontinuities and features which persist from the 'second' industrial revolution.
Technological revolutions and the evolution of industrial structures : assessing the impact of new technologies on the size, pattern of growth, and boundaries of firms / Giovanni Dosi [and others] -- The long-run dynamics of big firms : the 100 largest employers from the United States, the United Kingdom, Germany, France, and Japan : 1907-2002 / Howard Gospel and Martin Fiedler -- The long-term evolution of the knowledge boundaries of firms : supply and demand perspectives / Pamela Adams, Stefano Brusoni, and Franco Malerba -- Organizing the electronic century / Richard N. Langlois -- Aircraft and the third industrial revolution / Andrea Prencipe -- Aluminum and the third industrial revolution / Margaret Graham -- The role of the state in the third industrial revolution : continuity and change / Andrea Colli and Nicoletta Corrocher -- Celebrating youth : historical origins of the U.S. stock market's appetite for novelty / Mary A. O'Sullivan -- Labor in the third industrial revolution : a tentative synthesis / Stefano Musso -- A tentative conclusion / Louis Galambos.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Internet -- Social aspects; Information technology -- Social aspects; Industrial revolution